PENGARUH FINANCIAL DISTRESS, KARAKTERISTIK EKSEKUTIF, DAN KOMPENSASI EKSEKUTIF TERHADAP TAX AVOIDANCE PADA PERUSAHAAN JAKARTA ISLAMIC INDEX - Putri Meilia; Adnan Adnan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2017)
The research examines the effect of financial distress, executive characteristics, and executive compensation on tax avoidance. The sample of this research was taken from companies listed on Jakarta Islamic Index (JII) at 2011-2015. The sample was taken using purposive sampling. The sample used was 14 companies. In order to test the hypothesis, the statistical methods used was multiple linear regression analysis.The type of data used in this study is secondary data which is financial statement. Data analyzed by statistical analysis using multiple regression analysis. Then, data  processed by IBM Statistical Package for Social Science (SPSS) program. Partially the result of this research shows that financial distress, executive characteristics, and executive compensations have significant influence on tax avoidance. Meanwhile in the simultaneous test, the three independent variables are seen to have significant influences to the tax avoidance.